Auditoría tributaria y su incidencia en el cumplimiento de las obligaciones impositivas de la Avícola Villares, año 2022 - Tejada Licoa, Tania Tamara (2024)
An audit of tax compliance and the analysis of its impact on the fulfillment of tax obligations in Avícola Villares, year 2022 was conducted; the research addressed the following problem: In what way does the tax audit affect the fulfillment of tax obligations in Avícola Villares, year 2022? to meet the specific objectives; first the effectiveness of internal control in the accounting-tax area was evaluated, then the audit was performed and finally the report was issued. For the development of the research work, bibliographic information was used to obtain knowledge of the different authors, and with regard to the company's information, it was obtained through documentary, quantitative, field and descriptive research. With the execution of the audit, the final report was obtained in which the company's compliance with its tax obligations was evidenced, an adequate organization and execution of the accounting procedures was appreciated, the fulfillment of its tax obligations during the year 2022 and it was determined that the performance of a tax audit is a vital tool in the evaluation of an organization and its constant improvement.